Implementation of Guided Inquiry Strategy Combined with Scientific Student Worksheets on the Structure and Function of Plant Tissues to Improve Learning Outcomes - Muhibbuddin Muhibbuddin; Hafnati Rahmatan; Siti Zuhra (Postgraduate, University of Mataram, 2021)
This study aims to determine the application of a guided inquiry strategy combined with scientific student worksheets to improve student learning. The research method used is True experimental using pretest-posttest control group design. The population in this study were students of class XI MIPA MA Negeri 1 Pidie. The number of samples consisted of 132 people, and each class consisted of 33 students. The research instrument used is test questions. The data analysis technique of learning outcomes is through the N-Gain test and the independent sample t-test. The N-gain test of learning outcomes obtained that the average of the experimental class was higher than the control class, where each class was classified as a medium improvement criterion. The independent sample t-test showed a significant average difference between the learning outcomes of the experimental class and the control class, namely tcount > ttable (65.8 > 1.65). The percentage of N-Gain learning outcomes in the experimental class is 77.73% in the high category. This study concludes that there is an increase in student learning outcomes on the material structure and function of plant tissue at MAN 1 Pidie in the experimental class by applying the guided inquiry strategy combined with scientific Student Worksheets